2020
DOI: 10.1002/jcph.1773
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Feasibility of an Opportunistic Sampling Approach for Pharmacokinetic Studies of β‐Lactam Antibiotics in Critically Ill Children

Abstract: There has been increasing interest in incorporating β‐lactam precision dosing into routine clinical care, but robust population pharmacokinetic models in critically ill children are needed for these purposes. The objective of this study was to demonstrate the feasibility of an opportunistic sampling approach that utilizes scavenged residual blood for future pharmacokinetic studies of cefepime, meropenem, and piperacillin. We aimed to show that opportunistic samples would cover the full concentration‐versus‐tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 24 publications
2
40
0
2
Order By: Relevance
“…Our previous work has shown that there is high variability in plasma protein binding of other b-lactam antibiotics in the critically ill pediatric population (10), which is not unexpected given the high prevalence of hypoalbuminemia in critical illness (11). Since ceftriaxone is more highly bound to protein than many other b-lactam antibiotics, we sought to measure both total and free concentrations and develop separate concentrations but not free, unbound concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work has shown that there is high variability in plasma protein binding of other b-lactam antibiotics in the critically ill pediatric population (10), which is not unexpected given the high prevalence of hypoalbuminemia in critical illness (11). Since ceftriaxone is more highly bound to protein than many other b-lactam antibiotics, we sought to measure both total and free concentrations and develop separate concentrations but not free, unbound concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic sampling. Blood samples were obtained using scavenged opportunistic sampling as described previously (10,20). Briefly, all patients in the PICU who were administered at least one dose of ceftriaxone were screened to determine if the clinical team had ordered laboratory tests (e.g., complete blood counts and metabolic panels) after a ceftriaxone dose was given.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, 19 of the 23 studies were included; 4 studies that did not meet the inclusion criteria were used to support the concept of scavenged sampling. 8,9,11–31 Table 1 presents the characteristics of the 19 included studies. Table 2 presents the outcomes and limitations of included studies as described by the authors.…”
Section: Search Results and Selection Of Articlesmentioning
confidence: 99%
“…In addition, Tang-Girdwood et al demonstrated a broad distribution of antibiotic-free concentrations, particularly toward the end of the dosing intervals. 29 However, the authors indicate that there are possibly multiple factors contributing to the wide variability in free concentrations, including pathophysiological changes because of critical illness and variable protein binding, as well as patient factors.…”
Section: Gap Analysismentioning
confidence: 99%